RAPID SOLVENT-FREE MICROWAVE ASSISTED SYNTHESIS OF SOME N’-BENZYLIDENE SALICYLIC ACID HYDRAZIDES - Tutuk Budiati; Stephanie D.A.; Elisabeth Catherina Widjajakusuma (Indonesian Journal of Chemistry, 2012)
Condensation reaction has been carried out for the synthesis of some N'-benzylidene-2-hydroxybenzohydrazides using microwave assisted solvent-free method. The structures of all the products obtained in the present work are supported by spectral and analytical data (UV, IR, and 1H-NMR spectroscopy). The desired hydrazides are in 62-80% yields under microwave irradiation. The reaction was completed in 8-10 min.